Measuring progress from 1990 to 2017 and projecting attainment to 2030 of the health-related Sustainable Development Goals for 195 countries and territories: a systematic analysis for the Global Burden of Disease Study 2017 - GBD 2017 SDG Collaborators (2019)
GBD 2017 SDG Collaborators: Epidemiology Department (A C Garcia MPH), National Health Institute Doutor Ricardo Jorge (INSA), Lisbon, Portugal